Effect of Students Attitude Towards Mathematics on their Mathematical Achievement at Secondary School Level - Shah, Nazir Haider; Nazir, Nadia; Arshad, Mahek; Akhter, Khatiba; Shaheen , Abdul Khaliq; Younas, Sidra; Ghazanfar, Faheem (International Journal of Emerging Technologies in Learning (iJET), 2023)
The effect of student’s attitude on mathematical achievement has gathered tremendous attention from various researchers. However, there is a degree of inconsistency in the findings regarding these effects. The aim of the study was to find out the effect of students’ attitude towards Mathematics on their mathematical achievement at secondary schools in AJ&K. The objectives of the study were; to analyze students’ attitude in Mathematics at secondary level, to compare students’ attitude and academic achievement in Mathematics (gender wise) in AJ&K and to find out the effect of students’ attitude on Mathematical achievement at secondary level in AJ&K. The research was descriptive and quantitative in nature and cross-sectional survey was used to collect the data. All the students of 10th class of Govt. Secondary Schools in District Bagh AJ&K were the population of the study. There were 1076 students (458 boys and 618 girls) studying in 10th class in Government Secondary Schools of District Bagh. Sample was taken using Stratified random sampling technique. The researcher selected 444 students (192 male and 252 female) using proportionate stratified random sampling technique. The researcher developed five-point Likert scale questionnaire to collect the data. It was concluded that attitude had an impact on the mathematical achievements of the students. Parents’ education, qualification and social status had positive effect on academic achievements of students. It is recommended that students may be encouraged to achieve mathematical goals.